Water quality monitoring at Bukit Nenasi Highland irrigation in Kuala Terengganu - Mat Atar, Mat Amin; Mohd. Hudzari, Razali; Azizah, Endut; Noordin Asimi, Mohd Noor; Mohammad Moneruzzaman, Khandaker; Abdul Ssomad, M Abd Haliml; Nor Azuan, Husinl (2016)
The transfer of the knowledge is to improve filtration concept maintenance guide lslamic practice on daily solah just in time and investigate Bukit Nenasi highland area water quality based on ihe physico-chemical farameters and to relate its quality for human usage and consumption. The sampling was conducted in the middle of year 2016. Water samples were collected from two points: top of the hill and bottom part of the hill near the houses. The results showed that temperature, total dissolved solids (TDS), conductivity, dissolved oxygen (DO), pH, turbidity, total suspended solid (TSS), biological oxygen demand (BOD) and ammonia nitrate were in the permissible limits and according to the National Water Quality Standard (NWOS) were classified as class l. According to statistical data processing only TDS, conductivity and pH were significantly difference between the two levels and other parameters were not significantly difference. Therefore, the highland natural water at Bukit Nenasi is safe for domestic purposes and could be used for irrigation with advanced filtration system to solve the issues of clogging and maintenance.